Conductive nanomaterials for printed electronics - Kamyshny, Alexander (2014)
This is a review on recent developments in the field of conductive nanomaterials and their application in printed electronics, with particular emphasis on inkjet printing of ink formulations based on metal nanoparticles, carbon nanotubes, and graphene sheets. The review describes the basic properties of conductive nanomaterials suitable for printed electronics (metal nanoparticles, carbon nanotubes, and graphene), their stabilization in dispersions, formulations of conductive inks, and obtaining conductive patterns by using various sintering methods. Applications of conductive nanomaterials for electronic devices (transparent electrodes, metallization of solar cells, RFID antennas, TFTs, and light emitting devices) are also briefly reviewed.